ICT for Inclusion. A Student Voice Research Project in Spain - Teresa Susinos-Rada; Adelina Calvo-Salvador; Carlos Rodríguez-Hoyos; Ángela Saiz-Linares (Pontificia Universidad Javeriana, 2019)
This article is the result of a research project developed over 4 years (2011-15) in 13 schools in the region of Cantabria (Spain). In this research, students from different levels of education designed and implemented school improvement processes within a model of the student voice (SV) inspired by the pedagogy of participation and inclusion. This paper describes some of these experiences mediated by technology (photographs, 2.0 devices and video) in order to analyse what opportunities these devices offer as a means for contributing to a more participative and democratic school, where the student voice is a tool for change.